Zoomorphic Metamorphosis In The Albanian Oral Tradition Extraordinary Birth Of Extraordinary Children (Journal of Namibian Studies : History Politics Culture, 2023)
The motive of giving birth to a child in extraordinary circumstances has attracted the attention of Albanian storytellers and is very widespread in Albanian oral epics. It has a wide scope, especially in popular prose, namely in fairy tales. Despite its widespread in oral prose, this motif, in verse form, has a very limited spread and is found only in ballads. Tales of this motif belong to the type of mythical tales.